Encapsulación de aceite de Plukenetia volubilis L. (sacha inchi) en matrices de pectina recubiertas con sangre bovino y bioaccesibilidad de proteínas, lípidos y hierro - Valles Castillo, Carmenza (2022)
At present, in vitro digestion models are increasingly used by industries such as food and pharmaceuticals, to evaluate the bioavailability of active compounds present and / or incorporated in food and pharmaceutical products. The aim of this work was to produce, by ionic gelation, pectin microparticles containing sacha inchi oil electrostatically coated with bovine blood proteins. Furthermore, its bioaccessibility was determined using in vitro gastrointestinal digestion. The results for the size and encapsulation efficiency of uncoated microparticles were 186.94 ± 12.63 ?m and 81.63 ± 2.62%, respectively. After coating, it was observed that coated microparticles with bovine blood decreased in size (166.37 ± 19.07 ?m). Likewise, for coated microparticles, values of 57.58 ± 1.20% and 22.20 ± 0.64% were registered for proteins and lipids, respectively. The bioaccessible amounts of proteins, iron and lipids were 6.5 ± 0.85%, 12.55 ± 0.75% and 16.32 ± 0.96%, respectively, which were quantified in relation to the amounts contained in pectin microparticles. The data found in the present study, show that it is possible to develop food grade matrices for controlled release of hydrophilic and hydrophobic compounds, useful in the development of functional foods.